Current situation of gender equality in the board of directors of the agri-food cooperatives - Hernández Ortiz, María Jesús; Ruiz Jiménez, Carmen; García Martí, Elia; Pedrosa Ortega, Cristina (REVESCO. Revista de Estudios Cooperativos, 2018)
In recent years there has been a growing interest in increasing the participation of women in the decision-making areas and making visible their participation in rural cooperatives. As a consequence, fundamentally, the publication of Organic Law 3/2007, of March 22, for effective equality between women and men, is intended to promote compliance, development and implementation of this Organic Law in rural areas and also to give compliance with international agreements on gender equality. The administrations, social agents and organizations linked to the rural environment try to provide a favorable framework for reversing the situation suffered by women in all societies and cultures. This is accentuated in rural areas by the weak demographic situation and socioeconomic that characterizes it in most of the Spanish territory.In this study we analyze the information on the composition of the board of directors of the agri-food cooperatives included in the SABI database (Balance Sheets Analysis Systems) to know to what extent they are reaching or not this parity objective marked by the Law of Equality. In the same way, we relate the greater or lesser participation of women in the board of directors with other business characteristics (geographical location, activity sector, turnover, etc.) to verify the existence of possible significant differences depending on some of them. This paper contributes to the literature on and participation in the board of directors of cooperatives, an aspect hardly studied in previous studies.
Keywords: Women; Gender equality; Governance; Agri-food cooperatives.